Giant African Land Snail in Florida - John L. Capinera (EDIS)
They’re back! In 1966, a child smuggled three giant African land snails into south Florida which were released in their garden. Seven years later, more than 18,000 snails had been found and it took 10 years and $1 million to eliminate them. Florida is once again faced with an invasion by this snail. It feeds on hundreds of different plants and can transmit meningitis and other diseases to humans. Learn more in this 3-page fact sheet written by John L. Capinera and published by the UF Department of Entomology and Nematology, October 2011.